Bioactive Ingredients in Chinese Herbal Medicines That Target Non-coding RNAs: Promising New Choices for Disease Treatment - Dong, Yan; Chen, Hengwen; Gao, Jialiang; Liu, Yongmei; Li, Jun; Wang, Jie (Frontiers in Pharmacology, 2019)
Chinese herbal medicines (CHMs) are widely used in China and have long been a powerful method to treat diseases in Chinese people. Bioactive ingredients are the main components extracted from herbs that have therapeutic properties. Since artemisinin was discovered to inhibit malaria by Nobel laureate Youyou Tu, extracts from natural plants, particularly bioactive ingredients, have aroused increasing attention among medical researchers. The bioactive ingredients of some CHMs have been found to target various non-coding RNA molecules (ncRNAs), especially miRNAs, lncRNAs, and circRNAs, which have emerged as new treatment targets in numerous diseases. Here we review the evidence that, by regulating the expression of ncRNAs, these ingredients exert protective effects, including pro-apoptosis, anti-proliferation and anti-migration, anti-inflammation, anti-atherosclerosis, anti-infection, anti-senescence, and suppression of structural remodeling. Consequently, they have potential as treatment agents in diseases such as cancer, cardiovascular disease, nervous system disease, inflammatory bowel disease, asthma, infectious diseases, and senescence-related diseases. Although research has been relatively limited and inadequate to date, the promising choices and new alternatives offered by bioactive ingredients for the treatment of the above diseases warrant serious investigation.